STRATEGI PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) BERBASIS FINANCIAL TECHNOLOGY - Rezky, Muhammad Iqbal (Journal of Principles Management and Business, 2023)
This research aims to examine the development strategies of micro, small, and medium-sized enterprises (MSMEs) in Indonesia based on Financial Technology (FinTech). MSMEs play a significant role in the Indonesian economy but still face various challenges, particularly in terms of access to funding and technology. FinTech has emerged as an innovation in the financial sector that can help address some of these challenges. This study employs a qualitative descriptive approach with a literature review method. Data were collected from various secondary sources, including scholarly journals, books, and related research documents. The research findings indicate a stable and positive growth of MSMEs in Indonesia, with approximately 99.99% of business players in the country being part of this sector. MSMEs play a crucial role in creating jobs, increasing productivity, and supporting national economic growth. Furthermore, FinTech has played a key role in supporting the growth of MSMEs. Peer-to-peer lending (P2PL) platforms and digital payment solutions have provided easier and more efficient access to capital for MSMEs. Additionally, FinTech has transformed the way payments, transactions, and investments are carried out, helping to enhance efficiency and reduce risks. With broader financial inclusion and government support, MSMEs in Indonesia can continue to grow and thrive. FinTech has the potential to be a powerful tool in addressing some of the challenges faced by MSMEs, further strengthening its crucial role in the Indonesian economy.